Enhancing English Language Skills through Collaborative Strategic Reading at Makassar Tourism Polytechnic - Suparto, Windy Puspitasari; Amirullah, Amirullah; Basri, Muhammad; Salim, Muhammad Arfin Muhammad; Supriadin, Supriadin (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
Students in vocational higher education, particularly in tourism studies, often face challenges in comprehending English texts related to their field, such as brochures, menus, and service dialogues. This issue hinders their ability to engage in global communication and meet the professional demands of the tourism industry. This study aims to explore the implementation of Collaborative Strategic Reading (CSR) as an instructional strategy to enhance English language skills specifically reading comprehension, vocabulary development, and critical thinking in an English for Specific Purposes (ESP) context at Makassar Tourism Polytechnic. A qualitative descriptive method was employed, involving classroom observations, semi-structured interviews with students and lecturers, and document analysis. The findings indicate that CSR, through its four stages preview, Click and Clunk, Get the Gist, and Wrap Up effectively improved student engagement and comprehension of tourism-related texts. Students showed greater confidence in interpreting and summarizing English materials, while classroom interaction became more collaborative and student-centered. Document analysis also revealed more concise and focused student assignments, reflecting improved understanding and application of reading strategies. The study concludes that CSR is an effective and relevant approach to teaching English in tourism education, as it supports both linguistic and interpersonal skill development. The implication of this research suggests that integrating CSR into ESP curricula can better prepare tourism students for real-world communication tasks and professional interactions in international settings, ultimately enhancing their readiness for careers in the rapidly expanding global tourism industry.